2022
DOI: 10.1080/10872981.2022.2041366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antenatal Point-of-Care Ultrasound (PoCUS) training: a systematic review

Abstract: Introduction There is limited access to life-saving antenatal ultrasound in rural and low-resource settings largely due to shortages in skilled staff. Studies have shown healthcare practitioners can be upskilled in PoCUS through focused training, offering a viable solution to this deficit. However, standards for training and competency assessment are unclear and regulation surrounding practice is lacking. We aimed to review published literature examining antenatal PoCUS training programs, comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…However, the training required for POCUS certi cation can be costly, time consuming, utilizes patient resources and requires time away from the participant's practice (5,6). This is particularly relevant for providers in rural and remote communities, which are typically under-resourced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the training required for POCUS certi cation can be costly, time consuming, utilizes patient resources and requires time away from the participant's practice (5,6). This is particularly relevant for providers in rural and remote communities, which are typically under-resourced.…”
Section: Discussionmentioning
confidence: 99%
“…In-person POCUS modules typically cost $1500.00 (CDN) without consideration of costs accrued for the ultrasound machine, compensation to live models, instructor(s), or consumables associated with delivering such a course (e.g., catering, room rental, linens, ultrasound gel, etc.). Shortages in skilled staff, particularly in rural and low-resource areas, results in limited access to POCUS training (5,6). Online training may help overcome these barriers to POCUS education, which could be of special bene t for rural areas.…”
Section: Pocus Courses Such As Emergency Department Echo (Ede) and Th...mentioning
confidence: 99%
“…These studies commonly suffer limitations inherent to research conducted in remote settings, including low participant numbers, convenience samples, and loss to follow-up [ 32 ]. Our own systematic review [ 22 ] of PoCUS training evaluations in published literature highlighted a lack of comparable high-quality studies needed to establish a stronger evidence base for antenatal PoCUS. However, findings were generally positive, with improved knowledge and competence being reported despite the varying course durations (3 h to spanning several years).…”
Section: Discussionmentioning
confidence: 99%
“…Once trained it is challenging to entice professionals to relocate and remain in rural locations [ 18 , 20 , 21 ]. Upskilling the rural workforce in antenatal Point-of-Care ultrasound (PoCUS) is a viable solution to assist with this deficit and can offer substantial benefits to these under-resourced communities [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in obstetrics, studies have shown improvements in diagnosing complicated pregnancies, such as unfavorable fetal positions, placenta previa, and intrauterine growth restriction. However, there is still a lack of high-quality evidence demonstrating its accuracy compared to conventional high-resolution ultrasound devices [3,5,10,11]. In the evaluation of early pregnancy, authors have also highlighted the usefulness of POCUS in characterizing the intrauterine gestational sac [12][13][14].…”
Section: Introductionmentioning
confidence: 99%